2012
DOI: 10.1038/ncomms1981
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination and degradation of the FADD adaptor protein regulate death receptor-mediated apoptosis and necroptosis

Abstract: Fas-associated protein with death domain (FADD) is a pivotal component of death receptormediated extrinsic apoptosis and necroptosis. Here we show that FADD is regulated by makorin Ring Finger Protein 1 (mKRn1) E3 ligase-mediated ubiquitination and proteasomal degradation. mKRn1 knockdown results in FADD protein stabilization and formation of the rapid deathinducing signalling complex, which causes hypersensitivity to extrinsic apoptosis by facilitating caspase-8 and caspase-3 cleavage in response to death sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 56 publications
3
84
0
Order By: Relevance
“…Interestingly, FADD-depleted cells formed a more RIP1/RIP3 necrosome complex upon TNF activation in the presence of caspase inhibitor (72). Since FADD can bind to RIP1 and RIP3, FADD might directly modulate the interaction between RIP1 and RIP3 (72,79). Thus, we cannot exclude the idea that FADD might have caspase-8-independent role as well as caspase-8-dependent role in necroptosis.…”
Section: Proposed Mechanisms By Which Fadd Regulates Necroptosis In Amentioning
confidence: 61%
See 3 more Smart Citations
“…Interestingly, FADD-depleted cells formed a more RIP1/RIP3 necrosome complex upon TNF activation in the presence of caspase inhibitor (72). Since FADD can bind to RIP1 and RIP3, FADD might directly modulate the interaction between RIP1 and RIP3 (72,79). Thus, we cannot exclude the idea that FADD might have caspase-8-independent role as well as caspase-8-dependent role in necroptosis.…”
Section: Proposed Mechanisms By Which Fadd Regulates Necroptosis In Amentioning
confidence: 61%
“…We also recently reported that siRNA-or shRNA-mediated knockdown of FADD in L929 and HT-29 cells resulted in an increase in RIP1-RIP3 necrosome formation and necroptosis in the presence of caspase inhibitor, whereas FADD overexpression in L929 cells delayed RIP1-RIP3 necrosome formation and necroptosis (Fig. 2G versus 2D) (72). Since FADD is required for the activation of caspase-8, which is able to suppress necroptosis, FADD-deficient cells facilitate necroptotic cell death by abrogating caspase-8 function (Fig.…”
Section: The Roles Of Fadd On Apoptosis and Necroptosis In Vitro And mentioning
confidence: 99%
See 2 more Smart Citations
“…Like other Mkrns, LEP-2 has a RING domain that is typical of many E3 ligases (Bohne et al, 2010;Gray et al, 2000). Indeed, Mkrn1 in mammals functions as an E3 ligase, targeting several proteins and even itself, although has not yet been identified as one of its targets (Kim et al, 2005;Salvatico et al, 2010;Lee et al, 2009Lee et al, , 2012Ko et al, 2012;Shimada et al, 2009;Ko et al, 2010;Kim et al, 2014;Cassar et al, 2015). In other contexts, Mkrns are also RNA-binding proteins, are localized to ribonucleoprotein granules, and have been found to sequester some mRNAs or promote their translation (Cano et al, 2010;Cassar et al, 2015;Gajdos et al, 2010;Kwon et al, 2013;Miroci et al, 2012;Cheung et al, 2010;Yang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%